1993
DOI: 10.1007/bf00393549
|View full text |Cite
|
Sign up to set email alerts
|

Value of precraniotomy shunts in children with posterior fossa tumours

Abstract: Seventy children with posterior fossa tumours treated over a period of 6 1/2 years were studied. Most patients presented in the late stage of disease. Sixty-four required insertion of a precraniotomy shunt for one or more of the following: persistent vomiting, severe headache, dehydration, poor general condition, failing vision, altered sensorium, marked periventricular lucency, and brain stem involvement deferring total removal of the tumour. Insertion of precraniotomy shunt improved the general condition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
14
1
Order By: Relevance
“…20 Some studies have suggested that preoperative shunting can be encouraged. 21 Obviously, this resulted in 100% of the patients becoming either shunt-dependent or at least having a permanently inserted shunt after surgery for posterior fossa tumors. In 1985, the American Society for Pediatric Neurosurgery commissioned a study to try to determine which position was recommendable.…”
Section: Posterior Fossa Tumorsmentioning
confidence: 99%
“…20 Some studies have suggested that preoperative shunting can be encouraged. 21 Obviously, this resulted in 100% of the patients becoming either shunt-dependent or at least having a permanently inserted shunt after surgery for posterior fossa tumors. In 1985, the American Society for Pediatric Neurosurgery commissioned a study to try to determine which position was recommendable.…”
Section: Posterior Fossa Tumorsmentioning
confidence: 99%
“…3 Interestingly, almost half of the patients in this paper had shunts inserted in the OR on the day of presentation or the following day. One wonders if time could have been made for early resection, given that time for placement of a shunt was available.…”
mentioning
confidence: 87%
“…Unfortunately, primary resection of posterior fossa tumors is difficult to apply at our institution because we have the same problem as other developing countries, i.e., a very high referral rate of children with large posterior fossa tumors due to relatively late diagnosis, exceeding our tumor excision capacity and resulting in a long waiting list. 1,3 Tumor resection is typically performed on an elective basis in a special, wellequipped surgical theater by senior neurosurgical staff. Conversely, most children with severe hydrocephalus have shunts inserted by neurosurgical residents on an emergency basis, and most patients are typically discharged on the 2nd day and asked to return 1 day prior to the scheduled day of definitive surgery (approximately 10-14 days later).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Precraniotomy shunting has been largely abandoned and replaced by preoperative ETV or EVD as effective modalities for CSF diversion in more contemporary series. 1,9,15,16,25,33,36,39 Feng et al 11 concluded in their series of 58 patients (including both children and adults) that ETV prior to surgery is a most effective treatment for cases of preoperative obstructive hydrocephalus caused by aqueductal stenosis and space-occupying lesions. In the same study, shunt independence after ETV was achieved in 82% of patients with tumor-related obstructive hydrocephalus.…”
Section: Preoperative Hydrocephalus and Its Treatmentmentioning
confidence: 99%